A technology platform for standardized cryoprotection and freezing of large-volume brain tissues for high-resolution histology - Kumarasami, Ramdayalan; Verma, Richa; Pandurangan, Karthika; Ramesh, Jivitha Jyothi; Pandidurai, Sathish; Savoia, Stephen; Jayakumar, Jaikishan; Bota, Mihail; Mitra, Partha; Joseph, Jayaraj; Sivaprakasam, Mohanasankar (Frontiers in Neuroanatomy, 2023)
Understanding and mapping the human connectome is a long-standing endeavor of neuroscience, yet the significant challenges associated with the large size of the human brain during cryosectioning remain unsolved. While smaller brains, such as rodents and marmosets, have been the focus of previous connectomics projects, the processing of the larger human brain requires significant technological advancements. This study addresses the problem of freezing large brains in aligned neuroanatomical coordinates with minimal tissue damage, facilitating largescale distortion-free cryosectioning. We report the most effective and stable freezing technique utilizing an appropriate choice of cryoprotection and leveraging engineering tools such as brain master patterns, custom-designed molds, and a continuous temperature monitoring system. This standardized approach to freezing enables high-quality, distortion-free histology, allowing researchers worldwide to explore the complexities of the human brain at a cellular level. Our approach combines neuroscience and engineering technologies to address this long-standing challenge with limited resources, enhancing accessibility of large-scale scientific endeavors beyond developed countries, promoting diverse approaches, and fostering collaborations.